1983
DOI: 10.1210/endo-113-4-1519
|View full text |Cite
|
Sign up to set email alerts
|

HUMAN PANCREATIC GROWTH HORMONE-RELEASING FACTOR-40 (hpGRF-40) ALLOWS STIMULATION OF GH RELEASE BY TRH

Abstract: The effects of synthetic hpGRF-40 on GH release from continuously perifused male rat anterior pituitary cells were studied. Pulses (2.5 min) of hpGRF-40 stimulated GH release in a log-linear dose response relationship: concentrations of 0.03, 0.1, 0.3, 1, 3, 10, 30 and 100 nM given in a random order elicited a GH response above baseline of 1.2 +/- 0.3, 2.4 +/- 0.4, 2.8 +/- 0.2, 4.3 +/- 0.2, 6.2 +/- 0.7, 7.0 +/- 1.0, 8.7 +/- 1.7, and 10.8 +/- 0.8 micrograms/10(7) cells (mean +/- SEM; n = 3; r = 0.93), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 0 publications
4
17
1
Order By: Relevance
“…Although the intracellular mechanisms involved are still unclear, GRF exposure seems to facilitate the expression of GH-releasing activity by TRH. This hypothesis is sup ported by the present data and the finding that GH respon siveness to TRH, already observed in some in vitro experi ments [6], was greatly amplified by GRF hyperstimulation of cultured rat somatotrophs [4], The lack of effect of TRH on GH release during GRF infusion reported by others [18] can be attributed to differences in GRF exposure both in term of time course and doses utilized.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the intracellular mechanisms involved are still unclear, GRF exposure seems to facilitate the expression of GH-releasing activity by TRH. This hypothesis is sup ported by the present data and the finding that GH respon siveness to TRH, already observed in some in vitro experi ments [6], was greatly amplified by GRF hyperstimulation of cultured rat somatotrophs [4], The lack of effect of TRH on GH release during GRF infusion reported by others [18] can be attributed to differences in GRF exposure both in term of time course and doses utilized.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, GH increase after TRH has been hypothesized to result from defective somatostatin secretion allowing so matotrophs to respond to TRH [31], or from TRH-induced somatostatin inhibition leading to GH release [14], or from anatomical or functional disconnection from CNS struc tures or, more generally, from derangements in the central control of GH secretion [23,29], In particular, the hypothe sis that TRH may directly stimulate GH release acting on de-repressed specific TRH receptors of adenomatous so matotrophs has been put forward to explain the occurrence of GH increase after TRH in about 40% of acromegalic pa tients [11,12], However, as it has been very recently re ported that this aberrant response also occurred in patients with acromegaly due to growth hormone-releasing factor (GRF) hypersecretion from pancreatic and extrapancreatic tumors [13,26,28], it has been suggested that prolonged ex posure to GRF excess may sensitize somatotrophs to re lease GH in response to TRH. This hypothesis was strenghtened by the observation that GRF hyperstimula tion of cultured rat somatotrophs induced GH responsive ness to TRH [4], but challenged by the finding that TRH administered intravenously during GRF infusion to normal subjects did not elicit any GH release [18].…”
mentioning
confidence: 99%
“…In the rat, GH release is inhibited by TRH through an action in the hypo thalamus [2] but is increased by a direct action in the pitui tary when the gland is disconnected, either anatomically or functionally, from the hypothalamus [5]. A stimulatory ac tion of TRH has also been described in superfused dis persed pituitary cells provided the cells were first exposed to GRF [1], In preliminary work we have confirmed the lat ter observations which are in clear-cut contrast with the in hibitory action of TRH observed when TRH and VIP are superfused simultaneously. Possibly, TRH may be either stimulatory or inhibitory depending on the sequence as which the various peptides are presented to the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…In rats bearing hypothalamic lesions, more consistent GH stimulatory effects of TRH have been re ported [6,20], This stimulatory effect, however, was only confirmed in two in vitro studies using perifused rat ante rior pituitary fragments [4,23]. In perifused rat pituitary cells TRH stimulated GH release only after hp GRF-40 treatment [2]; in rat [23] or human [1] pituitary cell cultures TRH had no effect.…”
mentioning
confidence: 99%